PEWARISAN FONEM VOKAL PROTO AUSTRONESIA KE BAHASA JAWA DAN BAHASA MINANGKABAU - Tarihoran, Rezky Khoirina; Nurmala, Dewi; Dardanila, Dardanila; Sopha, Diana (Universitas Methodist Indonesia, 2023)
The purpose of this study is to explain the changes and inheritance of PAN vowels into Javanese (BJ) and Minangkabau (BM) languages. The approach used is the Comparative Historical Linguistics (LHK) approach. The data used is 200 swadesh vocabulary lists. The method used for data analysis is comparative historical method. The results of this study indicate that the inheritance of vowel phonemes in Javanese and Minangkabau languages ​​occurs in linear forms and innovative forms. Linear forms in Javanese are found in vowel phonemes /*a/, /*i/, /*e/, /*ə/ and /*u/ and innovative forms in Javanese are found on the vowel phonemes /*a/, /*i/, /*u/. the changes in vocal phonemes that occur in the innovative form occur in vocal phonemes /*a/ which change into vowel phonemes /o/, /ə/, and /e/. The vowel phoneme /*i/ changes to the vowel phoneme /e/ and the vowel phoneme /*u/ changes to the vowel phoneme /o/. For vowel phoneme forms in the Minangkabau language it is also found in linear and innovative forms where in vowel phonemes the linear form is found in the vowels /*a/, /*i/ and /*u/. In the innovative form it is found in the vowel phonemes /*a/, /*ə/, /*u/ where the vocal phonemes /*a/ and the vowel phonemes /*ə/ and /*u/. The changes in vocal phonemes that occur are the vocal phoneme /*a/ which changes to the vocal phoneme /o/, the vocal phoneme /*ə/ changes to the vocal phoneme /a/, and the vocal phoneme /*u/ changes to the vocal phoneme /o/.